Inventing modern - Lienhard, John H. (Oxford University Press, 2003)
1846 : great-grandpa and manifest destiny -- Short-lived technologies : searching for direction -- "The irruption of forces totally new" -- A new genus of genius -- Remington to modern : finding the core on the fringe -- Fires and the high-rise Phoenix -- The titan city -- Automobile -- On the road : of highways and gasoline -- The back door into the sky -- Flying down to Rio -- A boy's life in the new century -- Inventing a better mousetrap -- War -- A funeral in the fifties -- After modern